The prevalence and associated risk factors of female sexual dysfunction among healthcare personnel / Gurdeep Singh Grewal - Gurdeep Singh, Grewal (2012)
Sexual dysfunction is a complex disorder, influenced by a broad range of physical and psychosocial factors which adversely affects quality of life. Objective: To determine the prevalence and risk factors of female sexual dysfunction (FSD) among healthcare personnel in three government hospitals in Malaysia. Methods: 201 female healthcare personnel comprising doctors, allied health workers, nurses and ward assistants were randomly selected to participate in this cross-sectional study. Validated Malay Versions of the General Health Questionnaire-30, Female Sexual Function Index and the International Index of Erectile Function-5 were used to assess for depression and anxiety, sexual function in women and erectile dysfunction(ED) in their partners respectively. Statistical analysis was performed using SPSS version 16. Results: The prevalence of FSD was 5.5%, and women with sexual dysfunction were more likely to be married more than 20 years (OR=4.08; 95% CI; 1.15-4.50), have a frequency of sexual intercourse of less than once week (OR=5.00; 95% C; 1.05-23.76) and have a spouse suffering from mild to moderate ED (OR=24.35; 95% CI; 4.55-130.37). The prevalence of desire, arousal, lubrication, orgasmic and pain disorder was 18.9%, 3.5%, 2.5%, 2.0% and 3.0% respectively and of sexual dissatisfaction 3.5%. Conclusion: One in twenty female healthcare personnel suffered from FSD with low sexual desire being the most prevalent disorder and presence of ED in the partner negatively impacts her sexual function.